DG integration to distribution system with active power injection control - P. V. V Satyanarayana; P. V. Ramana Rao (Institute of Advanced Engineering and Science, 2020)
Conventional methodology for electrical power generation is vulnerable due to environmental limitations and the availability of fuel. Distributed generation, offering virtuous benefits to the market partakers, is trending in electrical power system in modern era. This paper presents the distributed generation integration to grid with active power injection control. Distributed generation source delivers DC power which is processed through square wave inverter. Inverter circuit is controlled using a simple control technique to match grid code. Fixing the current reference and varying the same, analysis is carried out for grid integration scheme of distributed generation injecting active power to grid. Simulation work is carried out and results are shown using MATLAB/SIMULINK software.